Peter Eckl: Research on the Pro-/Antioxidant Balance - Nikolaus Bresgen; Werner Siems (MDPI AG, 2022)
Peter Maria ECKL started his scientific career in the late 1970s at the Paris-Lodron University of Salzburg working in the field of radiation research [...]